Edukasi Kesehatan Reproduksi Pencegahan dan Penanggulangan Penyakit Infeksi Menular Seksual pada Ibu-Ibu Pasca Gempa di Cianjur - Nelil Mudarris; Dyan Oktaviany; Siti Khoiriyah; Tatik Dwiyani; Umaya Kumalasari; Rinasari Marliyani; Frina Erin Riani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
There was a 5.6 earthquake in the Cianjur area of West Java. This earthquake caused 327 fatalities, 13 people missing, more than 700 people injured and more than 2,000 houses damaged. In addition to causing casualties and material losses, this disaster also caused reproductive health problems. The most prominent problem occurred in mothers who complained of itching in the female area due to the lack of clean water supply after the earthquake. The purpose of this study was to improve reproductive health knowledge about the prevention and control of STIs in post-earthquake mothers in Cibulakan Village, Cugenang District, Cianjur. The method used by providing education using leaflet media related to reproductive health about the prevention and control of STIs in post-earthquake mothers. Education is given directly, the evaluation design of providing education is carried out by providing (pretest) and final evaluation (posttest) with the target, namely post-earthquake mothers in Cibulakan Village, Cugenang District, Cianjur. The statistical test is Paired sample T-test. The result was an increase in the knowledge of post-earthquake mothers after being given education by 48.7% so that at the end of the provision of education all post-earthquake mothers had high knowledge about reproductive health and prevention of sexually transmitted infections. The conclusion obtained is that there is an effectiveness of providing education using leaflet media in increasing knowledge.